MUSIC AS ALTERNATIVE TO IMPROVE THE QUALITY OF LIFE FOR ADULT PEOPLE WITH DISABILITIES - Moceviciene, Aldona (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
Each person's life pattern depending on the personalities are different from other individuals while life model is characterized by the same criteria: human individuality, human vital activity, an individual's ability to carry out those activities, activities influencing factors (biological, psychological, socio – cultural, environmental, political – economical), the individual's life expectancy. Optimizing the life quality of people with disabilities are three very important indicators which develops others to personal self-awareness, self-development and self-expression: integration into society, socialization and self-realization. Social Care House goal – to ensure the rational and efficient network of services that fully meet the needs of residents and allow full integration into community. Using music therapy techniques can be developed auditory and visual perception, language sharpness, motion flexibility and coordination and body control what can be applied meaningfully and efficiently in everyday life, at the same time as helping for a person to adapt in the environment and facilitating persons near communication. Object of research – individuals with moderate to profound intellectual disability optimization the quality of life through music / art therapy techniques. Study aims – to investigate adults with intellectual disabilities life quality optimization in the context of music therapy methods and techniques. In this work was used qualitative and quantitative research methods: theoretical, diagnostic, empirical.